Megineman Sebuah Komposisi Karawitan Kreasi Baru - I Putu Daniswara (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
The phenomenon of creating musical artwork in the Balinese musical art world can be inspired from previous work patterns. One of the patterns that can be used as a source of inspiration is the Gineman pattern. Gineman is a free interrupted melody played at the beginning of the song on Gender instruments. The gineman pattern which is only used as a prefix is a matter of concern for the composer. Therefore, a musical work was made in the form of experimental music entitled Megineman as an expression of anxiety from the pre-existing Gineman pattern. The medium used to express this artwork is Gamelan Genta Nada. To be able to transform this work, seven methods are used in the creation of Megineman musical artwork, namely nyelehin, nuasen, nuangin, nyujukin, nureksin, mayunin, and nabuhin. The result of the creative process that has been produced in this musical artwork creation with a duration of 12 minutes, consisting of three parts which are presented through video recordings in mp4 format with the title Megineman.